Expression levels of T cell-related immune factors and their correlation with thyroid function in Graves’ disease with varied serum iodine status: insights into immunopathogenesis - Wang, Lilan; Ru, Zixuan; Gao, Shengnan; Lv, Na; Li, Kerou; Qiao, Hong (Frontiers in Endocrinology, 2025)
ObjectiveMeasurement of Serum Iodine Concentration (SIC) in Newly Diagnosed Adult Graves’ Disease (GD) Patients with Hyperthyroidism and Healthy Controls: Investigating Cytokine Expression Profiles and Their Correlations with Thyroid Function Across Diverse Iodine Nutritional Status.MethodPatients newly diagnosed with GD hyperthyroidism from September 2024 to February 2025 at our institution were enrolled. Serum samples were collected for SIC measurement using arsenic-cerium catalytic spectrophotometry. Serum cytokine levels of 12 Th cell-related cytokines were quantified via LEGENDplex™ Human Th Cytokine Panel, and thyroid function was assessed by electrochemical immunoassay. Participants were stratified into three groups based on WHO iodine status criteria: iodine deficiency (<45 μg/L), adequate iodine (45-90 μg/L), and iodine excess (>90 μg/L). Pearson/Spearman correlation analyses were performed to evaluate associations between cytokine profiles and thyroid function parameters across subgroups.ResultsBased on the inclusion and exclusion criteria, a total of 75 subjects were enrolled in this study. The SIC was 148.62 ± 17.63 μg/L (GD I group), 72.33 ± 12.08 μg/L (GD II group), and 75.24 ± 7.94 μg/L (NC group), respectively, with statistically significant differences among the three groups (P<0.001). In GD patients, SIC showed a positive correlation with TRAb levels (r = 0.136, P<0.001). Serum concentrations of IL-6, IL-4, IL-5, IL-13, IL-2, IFN-γ, TNF-α, IL-17A, and IL-22 in GD patients were significantly higher than those in the NC group, with the GD I group demonstrating notably elevated IL-6 levels compared to the GD II group (P<0.05). Correlation analysis revealed positive associations between IL-6 and SIC, TRAb, and IL-17A (r = 0.114, 0.105, 0.214; P < 0.05), while no correlations were observed with FT3, FT4, TSH, TPOAb, or TgAb levels (P > 0.05). Similarly, IL-17A exhibited positive correlations with SIC and IL-6 (r = 0.130, 0.214; P < 0.05), but showed no significant associations with FT3, FT4, TSH, TPOAb, or TgAb concentrations (P > 0.05).Conclusions1. Serum cytokine levels (including IL-6, IL-9, IL-17A, IL-17F, and IL-22) exhibited significant differences between healthy subjects and patients with newly diagnosed hyperthyroid Graves’ disease (GD) under varying serum iodine concentration (SIC). 2. In newly diagnosed hyperthyroid GD patients, serum IL-6 demonstrated positive correlations with SIC, TRAb, and IL-17A (all P < 0.05), while IL-17A showed positive correlations with SIC and IL-6 (P < 0.05). 3. In GD patients with elevated SIC, cytokines IL-17A and IL-6 may contribute to pathogenic processes in hyperthyroid GD.